Changes in available nutrients along a chronosequence of poplar (Populus deltoids Bartr.) plantations in alluvial soils of Punjab - ., Shehnaz; Singh, Baljit (Indian Journal of Agroforestry, 2020)
The present study was conducted in district Ludhiana (Punjab) to investigate effects of cutting cycles of poplar (Populus deltoides Bartr.) and paddy-wheat sequence on the availability of macro and micronutrients. The treatments comprised of one, two, three and four cutting cycles (rotations) of poplar and paddy-wheat sequence. Surface and subsurface soil samples from farmers’ fields of two selected villages viz. Khehra Bet and Nurpur were collected and analyzed. The soils of selected villages are alluvial in nature as the river Satluj flows near these villages. Soil texture of surface (0-15 cm) soils of poplar rotations was sandy loam and that of paddy-wheat sequence was sandy clay loam. The results of the study indicated that there was a linear increase in the content of both macro as well as micronutrients with increase in number of cutting cycles. Significant increase in available N and P was observed in the four cutting cycles of poplar as compared to one cutting cycle. Available K did not increase significantly with increase in number of cutting cycles. The contents of micronutrients nearly doubled in four cutting cycles as compared to one cutting cycle up to 30 cm depth. In general, content of both macro and micronutrients decreased with increase in depth of soil. Further, the soils where paddy-wheat cropping sequence was followed for more than 25 years had either statistically similar or higher content of available nutrients than the four cutting cycles of poplar.